Religious Behavior in Traditional Treatment Systems in Rural Communities: A Study in Kadungora District, Garut Regency - Juhana Nasrudin (International Journal of Nusantara Islam, 2023)
The religious and social reality of rural communities are two things that always color the reality of traditional treatment systems in rural communities. So, in this regard it would be interesting to study and analyze so that the nature of the reality is found. The phenomenon of traditional medicine is a phenomenon which is an important condition to be revealed. To uncover the nature of reality, the authors conducted a study of the phenomenon using a phenomenological approach. So, from the results of the study, the authors found 3 important findings, namely: First, that the reality of the religious behavior of rural communities and social culture is inseparable from the elements of religion and myth. Second, that the reality of traditional medicine systems in rural communities is inseparable from the elements of religion, myth and magic. Third, that the understanding and experience of rural communities constructs the religious behavior of the community which will then reflect into the traditional medical system of rural communities. Then it can be drawn a conclusion that the reality of the traditional treatment system of rural communities is inseparable from the reality of experience and understanding of rural communities who are influenced by their religion and belief systems.